The pericellular environment regulates cytoskeletal development and the differentiation of mesenchymal stem cells and determines their response to hydrostatic pressure. - KELLY, DANIEL (My University, 2013)
The objective of this study was to examine the interplay between matrix stiffness and hydrostatic pressure (HP) in regulating chondrogenesis of mesenchymal stem cells (MSCs) and to further elucidate the mechanotransductive roles of integrins and the cytoskeleton. MSCs were seeded into 1 %, 2 % or 4 % agarose hydrogels and exposed to cyclic hydrostatic pressure. In a permissive media, the stiffer hydrogels supported an osteogenic phenotype, with little evidence of chondrogenesis observed regardless of the matrix stiffness. In a chondrogenic media, the stiffer gels suppressed cartilage matrix production and gene expression, with the addition of RGDS (an integrin blocker) found to return matrix synthesis to similar levels as in the softer gels. Vinculin, actin and vimentin organisation all adapted within stiffer hydrogels, with the addition of RGDS again preventing these changes. While the stiffer gels inhibited chondrogenesis, they enhanced mechanotransduction of HP. RGDS suppressed the mechanotransduction of HP, suggesting a role for integrin binding as a regulator of both matrix stiffness and HP. Intermediate filaments also appear to play a role in the mechanotransduction of HP, as only vimentin organisation adapted in response to this mechanical stimulus. To conclude, the results of this study demonstrate that matrix density and/or stiffness modulates the development of the pericellular matrix and consequently integrin binding and cytoskeletal structure. The study further suggests that physiological cues such as HP enhance chondrogenesis of MSCs as the pericellular environment matures and the cytoskeleton adapts, and points to a novel role for vimentin in the transduction of HP.
PUBLISHED
Keywords: Biomechanics; cytoskeleton; differentiation; stem cells; chondrogenesis; hydrogel; Biomechanics; cytoskeleton; differentiation; stem cells; chondrogenesis; hydrogel; Next Generation Medical Devices